Redefining Mathematics Teaching: How Online Professional Development Influences Teachers’ Efficacy, Burnout, and Reflection - Supratman Supratman; La Ode Sirad; Facharuddin Mustari (EDUPEDIA PUBLISHER, 2026)
Purpose: Online professional development has emerged as a promising approach for strengthening mathematics teachers' professional competence and supporting effective statistics instruction. This study examined the effects of online professional development on high school mathematics teachers' self-efficacy, burnout, and self-reflection, and explored its implications for improving statistical thinking instruction. Methodology: An explanatory sequential mixed-methods design was employed involving 21 mathematics teachers from three public senior high schools in Kolaka District, Indonesia. Quantitative data were collected using validated pretest–posttest measures of self-efficacy, burnout, and self-reflection, followed by semi-structured interviews to explain the quantitative results. Findings: Paired-sample t-tests revealed significant changes across all variables (p < .001). Self-efficacy increased from 118.00 to 130.00, self-reflection improved from 63.14 to 67.14, and burnout decreased from 317.05 to 294.05 following the intervention. Qualitative analysis identified three interconnected themes: strengthened teaching confidence, persistent workload-related burnout despite collegial support, and enhanced reflective practice. Significance: These findings indicate that online professional development effectively improves teachers' confidence and reflective capacity while promoting pedagogical competence in statistical education. Nevertheless, qualitative evidence suggests that professional workload remains a continuing challenge, underscoring the complexity of sustaining teacher well-being during professional learning. Overall, the findings demonstrate that well-designed online professional development can enhance instructional quality and foster supportive learning environments. Professional development initiatives should therefore integrate structured reflective activities, collaborative learning communities, and workload management strategies to maximize teacher learning while safeguarding psychological well-being.